Dual Catalysis for the Redox Annulation of Nitroalkynes with Indoles: Enantioselective Construction of Indolin‐3‐ones Bearing Quaternary Stereocenters. (6th August 2015) - Liu, Ren‐Rong; Ye, Shi‐Chun; Lu, Chuan‐Jun; Zhuang, Gui‐Lin; Gao, Jian‐Rong; Jia, Yi‐Xia
Abstract The enantioselective redox annulation of nitroalkynes with indoles is enabled by gold/chiral phosphoric acid dual catalysis. A range of indolin‐3‐one derivatives bearing quaternary stereocenters at the C2 position were afforded in good yields and excellent enantioselectivities (up to 96 % ee) from readily available starting materials.